Occupational lung disease among Basotho ex-miners in a large outreach medical assessment programme - Maboso, BM; Moyo, DM; Muteba, KM; Govender, VG; Barnes, DF; Maama-Maime, LBM; Makiti, SJ; Lerotholi, M; Ehrlich, R (Mettamedia (Pty) Ltd, 2022)
Background: Current initiatives in southern Africa to medically assess former migrant miners for silicosis and tuberculosis, including statutory and lawsuit- derived compensation programmes, require burden of disease information. To use clinical information collected on ex-miners examined at the Occupational Health Service Centre (OHSC) in Lesotho, operated under the Tuberculosis in Mining Sector in Southern Africa (TIMS) project, to measure the burden of lung disease and respiratory impairment. Methods: Demographic, occupational and medical history information, chest radiology, spirometry, GeneXpert testing for tuberculosis, and pulse oximetry outcomes were analysed, and descriptive summary measures calculated, in a group of ex-miners examined in 2017 and 2018. The study sample comprised 2 758 Basotho former underground miners, with median age of 62 years and median length of service of 28 years. Among ex-gold miners (n = 2 678), disease prevalence was high: radiologi- cal tuberculosis (consistent with previous or current disease) 60.9%, silicosis 42.5%, HIV 30.7%, silicotuberculosis 25.7%, and current active tuberculosis 6.8%. Of those with tuberculosis diagnosed microbiologically, 6.7% had no radiological evidence of tuberculosis and 54.1% did not report cough.